A qualitative study of patient preferences for prompts and reminders for a direct-mail fecal testing program - Davis, Melinda M (Transl Behav Med, 2020)
Programs that directly mail fecal immunochemical tests (FIT) to patients can increase colorectal cancer (CRC) screening, especially in low-income and Latino populations. Few studies have explored patient reactions to prompts or reminders that accompany such programs. As part of the Participatory Research to Advance Colon Cancer Prevention pilot study, which tested prompts and reminders to a direct-mail FIT program in a large, urban health center, we conducted telephone interviews among English- and Spanish-speaking participants who were assigned to receive a series of text message prompts, automated phone call reminders, and/or live phone call reminders. We analyzed interviews using a qualitative content analysis approach. We interviewed 41 participants, including 25 responders (61%) and 16 nonresponders (39%) to the direct-mail program. Participants appreciated program ease and convenience. Few participants recalled receiving prompts or automated/live reminders; nevertheless, the vast majority (95%, n = 39) thought reminders were acceptable and helpful and suggested that 2–3 reminders delivered starting 1 week after the mailed FIT would optimally encourage completion. Prompts and reminders used with mailed-FIT programs are accepted by patients, and my help boost response rates.